2003
DOI: 10.4315/0362-028x-66.7.1154
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Susceptibility of Salmonella Isolated from Foods in Korea from 1993 to 2001

Abstract: This study determined the prevalence of Salmonella in foods widely consumed in Korea from 1993 to 2001, along with antimicrobial susceptibility profiles of Salmonella isolates from these foods for 11 antibiotics. Overall, 41 Salmonella isolates, representing 15 serotypes, were obtained from 2.2% (29 of 1,334) of the samples examined, and most of the Salmonella isolates were recovered from broiler carcasses. The most common serotypes were Salmonella Enteritidis (29.3%), Salmonella Virginia (14.6%), and Salmonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 9 publications
5
23
1
1
Order By: Relevance
“…The results in this study show that multidrug-resistance is common in Salmonella isolates from poultry and swine, which are similar to those previously reported in Thailand [4,20] and from other countries [7,9,13]. High proportions of resistant S. enterica from swine and poultry were in agreement with a recent study conducted in Thailand that reported the highest resistance rate in Salmonella spp.…”
Section: Discussionsupporting
confidence: 82%
“…The results in this study show that multidrug-resistance is common in Salmonella isolates from poultry and swine, which are similar to those previously reported in Thailand [4,20] and from other countries [7,9,13]. High proportions of resistant S. enterica from swine and poultry were in agreement with a recent study conducted in Thailand that reported the highest resistance rate in Salmonella spp.…”
Section: Discussionsupporting
confidence: 82%
“…The reported rates of Salmonella contamination in retail meat and poultry are lower in more developed countries. In this study, 53.3% of poultry samples were contaminated with Salmonella, compared to only 23 to 29% in the United Kingdom (27, 41), 2.8 to 26.4% in Ireland (24, 29), 13.2% in The Netherlands (50), 35.8% in Spain (19), 36.5% in Belgium (48), and 36% in Korea (15). However, the rate was 60% in Portugal (5).…”
Section: Discussionmentioning
confidence: 72%
“…The rate of Salmonella contamination in retail meat samples above 60% is significantly higher than that reported for other countries (16,19,21,25,27,45,58,61). The antibiotic resistance susceptibility results also indicated alarming multiresistance frequencies for Salmonella and E. coli isolates from food, where multiresistance rates of 20.9% for Salmonella isolates and 61.6% for E. coli isolates were detected and most probably reflect the unregulated use of antibiotics in food-producing animals in the country (60).…”
Section: Discussionmentioning
confidence: 74%
“…Where they are reported, rates of resistance to antibiotics of bacteria originating from meat were high in developing countries (2,3,16,37,54), possibly as the result of the inappropriate or uncontrolled use of antibiotics in farming practices. Therefore, the study of antibiotic resistance in developing countries is important as the information could enhance prudent use of antibiotics in food production.…”
mentioning
confidence: 99%